Postmodernisme, Filsafat dan Universitas - Rodemeus Ristyantoro (Respons: Jurnal Etika Sosial, 2008)
Abstract: Modernism has brought the great accomplishment on science and technology. But modernism at the same time fails to bring pieceful and civilized life. As a reaction, postmodernism tries to promote a new world by giving space for mini naratin. University might play her role in this postmodernism era. She can promote local knowledge and local truth in all her activities : in recearch and teachingKata Kunci: Postmodernisme, modernisme, meta narasi, konteks lokal.